The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1021/ja00099a005
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Isotope Fractionation Factors for Benzylamine and Benzylammonium Ion. Comparison of Fractionation Factors for Neutral and Positively-Charged Nitrogen-Hydrogen Bonds

Abstract: Deuterium-protium fractionation factors were determined for benzylamine and benzylammonium ion by the traditional 1H N M R method and for the benzylammonium ion by a newly devised 13C N M R method. The results, 4phCH2NL2 = 0.958 f 0.070 and 4phCH2NL,+ = 1.081 f 0.019, when combined with the solvent isotope effect on the ionization of benzylammonium ion, also determined here, K H / K D = 3.36 f 0.13, give @ P~C H~N L , += 0.80 f 0.13 as the medium effect for transfer of this ion from H20 to D20. These results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…[α-13 C]Methyltrimethylammonium iodide was prepared previously. 4 The identities of these substances were confirmed by their 1 H NMR spectra. All other materials were best available commercial grades.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…[α-13 C]Methyltrimethylammonium iodide was prepared previously. 4 The identities of these substances were confirmed by their 1 H NMR spectra. All other materials were best available commercial grades.…”
Section: Methodsmentioning
confidence: 87%
“…than that for the neutral N᎐L bonds of benzylamine, 2, φ = 0.96. 4 Examination of vibrational frequencies of NL 4 + and NL 3 as surrogates for PhCH 2 NL 3 + and PhCH 2 NL 2 showed that the expected bond weakening accompanying positive charge introduction was indeed reflected in lowered stretching vibra- † The special symbol 'l ' is generally used for the fractionation factor of the hydronium ion. ‡ The symbol 'L' denotes either protium or deuterium, i.e.…”
mentioning
confidence: 99%
“…One factor that may increase or decrease φ, but is unrelated to bond stretching frequency differences in the solvent and solute sites, is a change in bending frequencies accompanying H-bond formation in the solute (52). For instance, fractionation studies on N,N-substituted benzylammonium ions by Kresge and co-workers have shown that anomalously high φ values may result from compensatory increases in bond bending vibration frequencies upon H bond formation (53,54). Thus, a strong hydrogen bond that undergoes a decrease in stretching frequency as compared to solvent may have a larger than expected φ value because of a compensatory increase in a bending vibration frequencies.…”
Section: N Chemical Shift and Scalar Coupling Constant Implicationsmentioning
confidence: 99%
“…The first is the difference in basicity of these amines. Benzylamine has a p K a of 9.36 (43), whereas that of H‐ l ‐Phe‐OEt is 2 units lower (7.23,44). This difference in p K a makes the environment of the Boc‐ l ‐Ser(Bzl)‐OH/benzylamine‐mediated condensation more basic than that of the Boc‐ l ‐Ser(Bzl)‐OH/H‐ l ‐Phe‐OEt (Table 2, entry 3), with the consequence that racemization increased to 1.8%.…”
Section: Resultsmentioning
confidence: 99%